2018
DOI: 10.15835/nsb10310296
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Dynamics and Species Diversity in a Saharan Oasis, Egypt

Abstract: The present study provides an analysis of the floristic composition, habitat types, vegetation structure and species diversity, elucidating the role of the environmental factors that affect species distribution in Kharga Oasis, Western Desert, Egypt. The vegetation was sampled from 89 permanently visited stands in 12 sites situated along N - S line transect across the oasis, and extending for about 185 km to cover as much as possible the physiognomic variation in habitats. Four main habitats were recognized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The overall floristic analysis of the study areas showed that the majority (48.2%) of the recorded flora belonged to five plant families: Asteraceae, Chenopodiaceae, Fabaceae, Zygophyllaceae, and Poaceae. This result was also consistent with those in adjacent areas in the arid region, e.g., El-Ghanem et al [78], Alatar et al [25], Shaheen et al [79], Zhang et al [71], Salama et al [80], and Croce et al [81] in Kuwait, Saudi Arabia, Pakistan, China, Egypt, and southern Italy, respectively. According to Pielou [68] and Magurran [69], the taxonomic range is higher in an area in which species are distributed among several genera than in which the most species belong to the same genus.…”
Section: Floristic Composition Biological Spectrum and Chorological Affinitiessupporting
confidence: 88%
See 1 more Smart Citation
“…The overall floristic analysis of the study areas showed that the majority (48.2%) of the recorded flora belonged to five plant families: Asteraceae, Chenopodiaceae, Fabaceae, Zygophyllaceae, and Poaceae. This result was also consistent with those in adjacent areas in the arid region, e.g., El-Ghanem et al [78], Alatar et al [25], Shaheen et al [79], Zhang et al [71], Salama et al [80], and Croce et al [81] in Kuwait, Saudi Arabia, Pakistan, China, Egypt, and southern Italy, respectively. According to Pielou [68] and Magurran [69], the taxonomic range is higher in an area in which species are distributed among several genera than in which the most species belong to the same genus.…”
Section: Floristic Composition Biological Spectrum and Chorological Affinitiessupporting
confidence: 88%
“…This study also indicated the disappearance of several plant communities that were previously of common occurrence, such as Retama raetam, Anabasis articulata, Ephedra alata, Artemisia monosperma, Zygophyllum decumbens, Lasiurus hirsutus, and Panicum turgidum. Most of the identified vegetation groups have analogues with others recorded in some wadis of the Eastern Desert [73,104], Western Desert [88,105], along the western Mediterranean region [106], in the South Sinai region [107,108], and in northwestern Negev, Israel [109]. This result can be directly related to the severe uncontrolled human disturbances (especially urbanization) along both sides of this road (Figure 6), where the vegetation is removed from nearly half of its length.…”
Section: Classification Of the Vegetationmentioning
confidence: 75%
“…Similar results found that introducing DSBP in rations of buffaloes and sheep resulted in an increase in CF content (10, 25). Also, replacing BH by DSBT in rabbit's ration decreased CF content and increased NFE and ash contents (13).…”
Section: Resultsmentioning
confidence: 97%
“…Community structure analysis: The three community structure indices used include, Margalefʼs diversity index (d), Shannon-Wiener index (H1) and Species Equitability (j) or Evenness 15,16 .…”
Section: Methodsmentioning
confidence: 99%